Bootstrap 4 projects - Vanston, Aaron; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Quite often when building various web applications, you will face the need to build out beautiful and mobile responsive websites in a small time frame. Bootstrap 4 helps alleviate the pain by defining sophisticated and refined user inputs and web components ready for your use. Learn how to quickly get your projects up to speed with the world's most popular front-end framework. Through this course, we will take you through not only Bootstrap 4's new features and changes, but create larger projects with these components and frameworks. These projects include building out the structure and design of a social media platform, comprehensive login and registration forms, and finally a music library application. Each project will provide you with a chance to use some of the new Bootstrap 4 components in the greater context of the Bootstrap framework."--Resource description page.
Title from resource description page (Safari, viewed April 18, 2017).
Presenter, Aaron Vanston.
Keywords: Bootstrap (Computer program); Web sites -- Design; Web site development; Electronic books